Effect of crystalline admixtures on the self-healing capability of early-age concrete studied by means of permeability and crack closing tests. (1st July 2016) - Roig-Flores, M.; Pirritano, F.; Serna, P.; Ferrara, L.
Highlights: Self-healing is analyzed by permeability and crack closing in concrete specimens. Self-healing has been compared for two concrete classes healing underwater. Healing has been evaluated under water immersion at 15 °C, 30 °C and wet/dry cycles. The results are compared with previous tests, comparing a total of six exposures. Abstract: This paper analyzes the self-healing properties of early-age concretes, engineered using a crystalline admixture (4% by the weight of cement), by measuring the permeability of cracked specimens and their crack width. Two concrete classes (C30/37 and C45/55) and three healing exposure conditions have been investigated: water immersion at 15 °C, at 30 °C and wet/dry cycles. Specimens were pre-cracked at 2 days, to values of crack width in the range of 0.10–0.40 mm. The results show almost perfect healing capability for specimens healed under water at 30 °C, better than for specimens healed under water at 15 °C, while insufficient for the wet/dry exposure.